Live working on vintage 138 kV steel lattice structures. - Gela, G.
Live working on very old structures often poses unique challenges, such as dealing with the effects of arc rings and the behavior of old insulators. This paper presents the results of tests conducted for Public Service Electric and Gas to confirm that very old broken insulators can be replaced live on 138 kV double-circuit steel lattice structures with suspension I-strings. Each string had nine porcelain units and two large arc rings with a clear air ring-to-ring distance of 1.07 m (42''). Issues addressed in this paper include: the effects of broken and shorted insulators; the effects of live working tools and workers; and the possibility of selective barehanding. For the above-listed conditions, switching impulse tests were performed on a full-scale mockup of the structure. Actual hardware retrieved from service was used for the mockups. Workers were represented by mannequins. The paper gives switching impulse test results for the outlined conditions. Test data suggest that there is little difference between broken and shorted insulators in the tested cases. However, the CIGRE formula for calculation of the effects of defective insulators is shown to be sufficiently conservative
Keywords: 1.07 m; 138 kV; 42 in; CIGRE formula; Public Service Electric and Gas; Arc rings; Broken insulators; Clear air ring-to-ring distance; Double-circuit steel lattice structures; Live line maintenance; Live working; Live working tools; Mannequins; Old insulators; Porcelain units; Selective barehanding; Shorted insulators; Suspension I-strings.; Switching impulse tests; Switching sparkover; Vintage steel lattice structures